A Controlled Trial of Polyglytone 6211 versus Poliglecaprone 25 for Use in Intradermal Suturing in Dogs - Pagona Gouletsou (MDPI AG, 2021)
The objective of this work was the comparative evaluation of the healing process after employing 4/0 poliglecaprone 25 and 4/0 polyglytone 6211 in a continuous intradermal suture pattern. Ten Beagle dogs were used, in which skin incisions were created surgically and subsequently were sutured by means of continuous intradermal pattern using polyglytone 6211 or poliglecaprone 25 suture. Cosmetic, clinical, and histologic scores were evaluated. The cosmetic appearance of the wounds was blindly evaluated on days 7, 14, 28, 180, 360, 730, and 1095. On the same days, tissue biopsy was performed for histological evaluation. Clinical evaluation was performed initially daily, then weekly, monthly, and finally yearly, till day 1095. The clinical appearance of the intradermal pattern with both sutures was initially very good, deteriorated in the second post-operative month and thereafter improved. The cosmetic, clinical, and histological differences between the two suture materials were minimal and statistically insignificant. Polyglytone 6211 is sufficient for use in intradermal suturing in dogs. However, its earlier absorption compared to poliglecaprone 25 did not have any beneficial effect on cutaneous wound healing and scar appearance in the experimental animals.